REVIEW: No return to ‘normal’ when the pandemic has exposed global inequalities - Krishan Dutta (Asia Pacific Network, 2021)
COVID-19, Racism and Politicization: Media in the Midst of a Pandemic, edited by Kalinga Seneviratne and Sundeep R. Muppidi. Newcastle-upon-Tyne, UK: Cambridge Scholars Publishing. 2021. 230 pages. ISBN: 9781527570894